Analisis Bauran Pemasaran dalam Pengembangan Layanan Private Wing di Rumah Sakit Nasional Diponegoro - Muhammad Farras Razin Perdana; Sutopo Patria Jati; Septo Pawelas Arso (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
The hospital is one of the businesses engaged in the health sector by emphasizing the products and health facilities that are able to be provided by the hospital. Considering the high level of competition in hospitals in Indonesia, both state-owned and private hospitals, many hospitals have developed marketing strategies to meet sales targets and realize marketing goals. One of them is the Diponegoro National Hospital which runs a Global Innovative Marketing strategy by providing exclusive Private Wing services for special customers or VIPs (Very Important Person). In this case, the researcher reviews the marketing mix of Private Wings Services through seven variables, namely product, price, place, physical evidence, people, promotion, process. The process of collecting data was carried out by in-depth interview techniques and literature studies on several related literatures that were used as research references. The research was conducted qualitatively and the data that had been collected were analyzed descriptively. The results of this study indicate that the promotion and place variables need to be a concern for the Diponegoro National Hospital in developing Private Wing services.